The Politics of Contestation in Asia: How Japan and Pakistan Deal with their Rising Neighbors - Hannes Ebert; Daniel Flemes; Georg Strüver (German Institute of Global and Area Studies (GIGA), 2012)
Rising powers have attracted tremendous interest in international politics and theory. Yet the ways in which secondary powers strategically respond to regional changes in the distribution of power have been largely neglected. This article seeks to fill this gap by presenting a systematic comparative analysis of the different types of and causes of contestation strategies undertaken by secondary powers. Empirically, it focuses on two contentious regional dyads in East and South Asia, exploring how structural, behavioral, and historical factors shape the way in which Japan and Pakistan respond, respectively, to China's and India's regional power politics. The paper concludes that the explanatory power of these factors depends on the particular context: in the case of Japan, China's militarily assertive regional role has invoked the most significant strategic shifts, while in the case of Pakistani contestation, shifts in polarity have had the largest impact on the strategic approach.
Keywords: 300